2011
DOI: 10.1109/tvcg.2011.234
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Highlighting: 2D Graph Visualization on Stereo Displays

Abstract: Fig. 1. The stereoscopic highlighting technique illustrated with separate images for the left and right eye. The highlighted yellow node and all of its immediate neighbors are rendered at a depth closer to the viewer. The two images above represent a stereo pair. By crossing eyes, the reader can perceive the 3rd dimension of the stereoscopic highlighting.Abstract-In this paper we present a new technique and prototype graph visualization system, stereoscopic highlighting, to help answer accessibility and adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 26 publications
1
66
0
1
Order By: Relevance
“…The benefit of using 3D for visualizing (complex) content has been demonstrated in many domains such as in medicine [14] or graph visualization [1]. The use of 3D displays in the automotive domain has been investigated by Broy et al [2], who identified benefits regarding attractiveness when visualizing an in-vehicle information system's menu structure on a 3D display, compared to 2D displays.…”
Section: Application Of 3d Displaysmentioning
confidence: 99%
“…The benefit of using 3D for visualizing (complex) content has been demonstrated in many domains such as in medicine [14] or graph visualization [1]. The use of 3D displays in the automotive domain has been investigated by Broy et al [2], who identified benefits regarding attractiveness when visualizing an in-vehicle information system's menu structure on a 3D display, compared to 2D displays.…”
Section: Application Of 3d Displaysmentioning
confidence: 99%
“…Tiled LCD walls are considered better as compared to CAVEs as far as the image quality is concerned. They offer higher image quality and better resolution up to thousand mega pixels [3].…”
Section: Big Data In Computer Graphicsmentioning
confidence: 99%
“…Prior work has shown a combination of salient features (e.g., color and depth) to significantly decrease search times [1,13]. A UI can hence employ depth layers to group or highlight urgent or frequently used objects.…”
Section: Supporting Layered 3d Interfacesmentioning
confidence: 99%
“…As a result, gaze as input modality for public displays has recently received considerable attention [21]. At the same time, the advertising industry started to deploy auto-stereoscopic displays at airports and in train stations 1 . We envision this technology to be soon deployed also for information displays, where users could access transport schedules, store directories, or city maps.…”
Section: Public Displaysmentioning
confidence: 99%